Eminescu – poezia naşterii şi a stingerii (elemente de antropogonie eminesciană) - Carmina Cojocaru (Revista de Istorie și Teorie Literară)
Antropogonia eminesciană represents a chapter of the PhD Thesis with the title Poezia naşterii şi a stingerii la Eminescu. It develops upon the view that the root of Eminescu’s entire work is an obsessive, complex artistic vision about man. The antropogonic concern, characteristic to great thinkers everywhere and since forever, follows the individuality of human essence and the revealing of man’s interest for his own person. For Eminescu, these matters are triggered very timely, since the age of 15 when, in a posthumous version of the poem Din străinătate and then in Amicului F.I. he would ask himself: „Ce este omul? Ce-i omenirea?/ Ce-i adevărul? Dumnezeirea?”. In other words, the primordial purpose searched by the lirical, epic, dramatic and even journalistic developments is that of apprehending the human being. It is an inner stimulus that guides him through the diverse researches and studies underwent throughout his life. The attitude adopted was innitially interrogative but further became meditative, analitic, with the aim of reaching a complete comprehension of the significance of the existance, of human contradictions and of discovering new divine ideals. Eminescu begins from the idea that death is nothing more than an egress from time, and life – its acknowledgement. Many texts, especially those from manuscripts, contain reflections upon time, life, death, and are perceived in their ambivalence. In works such as Memento mori, Povestea magului călător în stele, Luceafărul, Rime alegorice, Împărat şi proletar, Glossă, Mortua est!, which as an initial form (that of “meditation”) – Elena is also the first antropogonic poem, Demonism, Epigonii the two major human essences become beginnings and ends of conscious and over conscious at the same time. In Preot şi filosof, Scrisoarea I, Odin şi Poetul Eminescu reaches the firm belief that being aware of his predestined limits, the world on the whole, does not concentrate its efforts towards deeper spiritualization, but on the contrary, it plunges in an ocean of contradictions. The poet reached the highest degree of understanding life, the essence drawn out of a long line of other existing essences which, in our opinion, makes the most complex, shattering confession whose deep meaning is represented by human essence and becomes part of the Eminescu antropogonic foundation: comprehending life as „part of the whole” that would immediately lead to the complet understanding of death, and from here to the staggering elevation of the most stirring verse: “Nu credeam să-nvăţ a muri vreodată”. The revelation of death in the embodiment of the spirit generates an inner revolution, a shattering and transformation so complex that outshine the voluptuousness of all other experiences. While searching for the meaning of the world and time, of birth and of death in the “fever of antropogonic obsession” it was impossible not to encounter the desire of discovering who is on the other side from the “closed gate”, where there was „God’s dogma” (Sărmanul Dionis). At the same time, there appear questions regarding our Creator and antology meditation, as it is the case in Memento mori, but also furious outbursts like in Demonism. Through all of these searches, Eminescu places a permanent antropogonic vision at the foundation of his creation on which are based both the cosmogonic and sociogonic views that G. Calinescu and Tudor Vianu discuss.